Tinjauan Konseptual terhadap Kaidah-Kaidah Fikih yang Khusus dalam Bidang Hukum Keluarga Islam - Haliza Nur Madhani; Syaifullah Syaifullah; Hikmal Asril Annaza; Lisnawati Lisnawati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic family law is one of the crucial fields within Islamic law in the lives of Muslims, as it regulates family relationships, such as marriage, divorce, maintenance, child custody, inheritance, and guardianship. In the dynamics of Muslim life, family law is not only about matters of worship and social ethics but also related to justice and the protection of individual rights within the family sphere. Thus, a comprehensive approach is needed in the study of Islamic family law that is not only based on textual evidence but also on fiqh principles that can serve as a foundation in establishing Islamic law. The purpose of this research is to examine the specific fiqh principles in the field of Islamic family law, which include concepts, application examples, and the role of these fiqh principles in the context of Islamic family law. This research uses normative legal methods in qualitative form, with data obtained through library studies followed by content analysis to draw research conclusions. The research findings indicate that specific fiqh principles in the field of Islamic family law play an important role in establishing laws and resolving various issues within the family context.